Foliar Application or Seed Priming of Cholic Acid-Glycine Conjugates can Mitigate/Prevent the Rice Bacterial Leaf Blight Disease via Activating Plant Defense Genes - Pal, Garima; Mehta, Devashish; Singh, Saurabh; Magal, Kalai; Gupta, Siddhi; Jha, Gopaljee; Bajaj, Avinash; Ramu, Vemanna S. (Frontiers in Plant Science, 2021)
Xanthomonas Oryzae pv. oryzae (Xoo) causes bacterial blight and Rhizoctonia solani (R. solani) causes sheath blight in rice accounting for >75% of crop losses. Therefore, there is an urgent need to develop strategies for the mitigation of these pathogen infections. In this study, we report the antimicrobial efficacy of Cholic Acid-Glycine Conjugates (CAGCs) against Xoo and R. solani. We show that CAGC C6 is a broad-spectrum antimicrobial and is also able to degrade biofilms. The application of C6 did not hamper plant growth and showed minimal effect on the plant cell membranes. Exogenous application of C6 on pre-infection or post-infection of Xoo on rice susceptible genotype Taichung native (TN1) can mitigate the bacterial load and improve resistance through upregulation of plant defense genes. We further demonstrate that C6 can induce plant defense responses when seeds were primed with C6 CAGC. Therefore, this study demonstrates the potential of CAGCs as effective antimicrobials for crop protection that can be further explored for field applications.